The Impact of Stigma on Medication Compliance for Tuberculosis Patients at the Health Center in Bandar Lampung City - Umar, Ernawati; Romadhon , Rhinaldy Danara; Yupartini , Lisnawati; Darajat , Ahmad (JURNAL INFO KESEHATAN, 2023)
Tuberculosis, a lethal infectious illness, is known as the ninth leading cause of mortality worldwide. Self-stigma might emerge from the social stigma that Tuberculosis patients experience in their social environment. Stigma is triggered by five factors: self-isolation, supportive views, discrimination experiences, social withdrawal, and stigma resistance. The purpose of this study was to see how Tuberculosis stigma affected medication adherence at Bandar Lampung City Health Center. This study is a quantitative study employing a case-control technique. The simple random sampling technique was utilized with a total sampling of up to 54 respondents who fulfilled the inclusion criteria. Data collection through the completion of the questionnaire. A bivariate chi-square test and a multivariate logical regression test were utilized to analyze the data. The findings indicated age, sex, marital status, education, occupation, self-isolation, views of support, experience of discrimination, social withdrawal, and rejection Stigma: p-value of self-isolation = 0.000, views of support = 0.000, experience of discrimination = 0.007, social withdrawal = 0.001, resistance to stigma = 0.000. The value of the logistic regression equation is Y = a + b1 X + b2 X + b3 X. This study concludes that stigma resistance is the most influential factor impacting medication adherence. This study suggests that tuberculosis sufferers do not withdraw, may contribute to society, socialize more, get along conveniently, and overcome stigma by thinking positively.